Analysis of the Potential and Influencing Factors of Regional Logistics Industry Development from the Perspective of Supply Chain. (15th September 2022) - Jiang, Fang
Abstract : The logistics sector has grown to be the most significant component of the modern service sector, and to some extent, it not only directly supports economic growth but also indirectly creates favorable conditions for business operations. Modern logistics can meet the needs of the modern economy and society by taking advantages and prospects of digitization and information technology. However, China has a number of difficulties while switching to the development of logistics since the level of modern Chinese logistics development differs. Additionally, the supply chain mode's logistics is a comprehensive and integrated operation, so based on the issues with Chinese regional logistics development from a supply chain viewpoint, this study evaluates the development potential of logistics supply chain and the influencing factors from many angles.